Intravenous leiomyomatosis involving the inferior vena cava and right atrium with postoperative pulmonary embolism: a case report - Chen, Yukai; Zhang, Wangwei; Zhuang, Aobo; Liu, Jiaqing; Wang, Qinlei; Xia, Xiaogang; Li, Wen'gang (Frontiers in Surgery, 2026)
Intravenous leiomyomatosis (IVL) is a rare subtype of benign smooth muscle tumor that can exhibit malignant-like biological behavior. Originating in the uterus, IVL grows in mass-like formations within small veins and can extend into the inferior vena cava (IVC), right atrium, and pulmonary arteries. Due to the potential for life-threatening consequences when IVL invades the heart and pulmonary arteries, early diagnosis and radical resection through a multidisciplinary approach are crucial. This report presents a case of uterine intravenous leiomyomatosis involving the IVC and right atrium, complicated by massive pulmonary embolism after surgery, and includes a literature review to discuss the clinical implications.